Comprehensive investigation on metabolites of Panax quinquefolium L. in two main producing areas of China based on ultra‐high‐performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry. (14th December 2021) - Si, Yu; Jiao, Yufeng; Li, Le; Lin, Hongqiang; Wang, Cuizhu; Zhou, Baisong; Liu, Yunhe; Li, Zhuo; Li, Pingya
Abstract: Jilin Province and Shandong Province are two main American ginseng (AG) producing areas in China. The geographical difference existed in these two provinces. Aiming at evaluating the similarities and differences of the secondary metabolites, the comprehensive metabolite profiling of AG from Jilin Province (AGJ ) and Shandong Province (AGS ) was performed based on UPLC‐QTOF‐MS for the first time. In screening analysis, a total of 111 shared compounds, with ginsenosides being major components, were identified or tentatively characterized, which indicated that AGJ and AGS were all rich in phytochemicals and contained similar structural types. Untargeted metabolomics analysis indicated that there were significant differences in the contents of certain constituents in AGJ and AGS . Nineteen (12 for AGJ, 7 for AGS ) potential producing area‐dependent chemical markers were discovered. Based on the contents and MS responses, ginsenoside Rg1, Re, and pseudoginsenoside F11 could be considered as the characteristical markers of AGJ, whereas ginsenoside Rg3 and Rh2 of AGS . This comprehensive phytochemical profile study could provide valuable chemical evidence for evaluating the characteristics qualities of AG from various producing areas.